On the weighted mixed liu-type estimator under unbiased stochastic restrictions - YILDIZ, NİLGÜN (Taylor and Francis Inc., 2017)
In this article, we introduce the weighted mixed Liu-type estimator (WMLTE) based on the weighted mixed and Liu-type estimator (LTE) in linear regression model. We will also present necessary and sufficient conditions for superiority of the weighted mixed Liu-type estimator over the weighted mixed estimator (WME) and Liu type estimator (LTE) in terms of mean square error matrix (MSEM) criterion. Finally, a numerical example and a Monte Carlo simulation is also given to show the theoretical results. © 2017 Taylor & Francis Group, LLC.
Keywords: Liu-type estimators; Mean square error matrix; Ordinary mixed estimator; Weighted mixed estimator; Weighted mixed Liu estimator; Weighted mixed Liu-type estimator